2005
DOI: 10.1007/s10517-005-0391-2
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Activity of Microvessels and Angiogenesis in Eutopic Endometrium in Patients with Peritoneal Endometriosis

Abstract: Comparative analysis of the density of microvessels and angiogenic activity in eutopic endometrium during different phases of the menstrual cycle in patients with peritoneal endometriosis showed that peritoneal form of endometriosis is a paracrine disease with dysregulation of angiogenesis processes in the eutopic endometrium. Excessive angiogenesis in this condition promotes implantation of eutopic endometrium on the peritoneum. Angiogenesis in eutopic endometrium can be maintained due to high concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
1
3
0
2
Order By: Relevance
“…Although there is convincing evidence of increases in a number of angiogenic parameters in the eutopic endometrium of women with endometriosis, previous studies have shown conflicting findings regarding endometrial blood vessel density (BVD). Some groups have described significantly increased endometrial BVD in women with endometriosis (18,19,22), while other studies have found no significant differences in endometrial BVD compared to controls (23,24). Thus, the aim of this study was to investigate for the first time uterine lymphatic vessel density (LVD) in endometriosis, as well as to clarify controversy in the literature regarding the density of blood micro-vessel populations in women with endometriosis.…”
Section: Immunohistochemistrymentioning
confidence: 98%
“…Although there is convincing evidence of increases in a number of angiogenic parameters in the eutopic endometrium of women with endometriosis, previous studies have shown conflicting findings regarding endometrial blood vessel density (BVD). Some groups have described significantly increased endometrial BVD in women with endometriosis (18,19,22), while other studies have found no significant differences in endometrial BVD compared to controls (23,24). Thus, the aim of this study was to investigate for the first time uterine lymphatic vessel density (LVD) in endometriosis, as well as to clarify controversy in the literature regarding the density of blood micro-vessel populations in women with endometriosis.…”
Section: Immunohistochemistrymentioning
confidence: 98%
“…This includes: (1) existing vessel endothelial cell basal membrane degradation and fragmentation influenced by the action of metalloproteases; (2) endothelial cell migration to the stromal tissue and extracellular matrix proteolytic degradation; (3) endothelial cell proliferation, new capillary tube formation, fusion of the formed vessels and its network development; (4) endothelial cell proliferation and migration suppression and fate under the influence of the angiogenic factors [44-47]. …”
Section: Angiogenesis Stagingmentioning
confidence: 99%
“…For this reason, the mechanisms leading to adenomyosis-associated infertility have been explained in similar physiopathological terms to those of endometriosis (20)(21)(22)(23)(24). More recently, it has been suggested that an inadequate blood supply to the endometrium interferes with implantation (25,26), but functional studies addressing the effects of adenomyosis on endometrial receptivity are scarce.…”
mentioning
confidence: 99%